Existence and regularity for a chemotaxis model involved in the modeling of multiple sclerosis - Valeria Giunta (Ricerche di Matematica, 2021)
We study in this work the global existence of solutions to a system of reaction cross diffusion equations appearing in the modeling of multiple sclerosis, in the one-dimensional case. Weak solutions are obtained for general initial data, and existence, uniqueness, stability and smoothness are proven when initial data are smooth.